Chemical Pneumonia Due to Paint Thinner Ingestion: A Case Report and Literature Review - Mehmet Koçak; Kurtuluş Açıksarı (Eurasian Journal of Emergency Medicine, 2019)

(untitled)
Paint thinner is an organic solvent which includes aromatic hydrocarbons and is widely used in the paint, varnish, and plastic products industries. Regular inhalation of such solvents is known to cause chronic intoxication. Oral thinner over-exposure is rare but quite fatal. Volatile liquids can cause pulmonary complications even with oral ingestion. Therefore, in patients with oral volatile liquid thinner intake, emergency physicians should be aware of local complications as well as the systematic effect even with initial normal physical or radiological findings. In this report, we present a patient with chemical pneumonia due to self-vomiting after accidentally drinking paint thinner.